Pengaruh Self-esteem dan Psychological Well Being terhadap Job Performance melalui Work Engagement pada Pegawai Bank di Kota Surabaya - Amalia, Firdha; Budiono, Budiono (Jurnal Ilmu Manajemen, 2021)
This study aims to study the effect of and psychological well-being on job performance through work involvement in bank employees in Surabaya. This study uses a type of causality research that uses quantitative. Sampling technique using accidental sampling. Amount of respondents is 81 bank employees in Surabaya. The statistical analysis in this study is used the Structural Equation Model (SEM) with the help of Smart PLS 3.2.9 software. The results showed that Self-esteem was not a significant positive effect on job performance. Self-esteem has a positive and significant effect on work engagement. The psychological well being did not have a positive effect on job performance. Psychological well being has a positive and significant effect on work engagement; work engagement has a positive and significant effect on job performance, has an indirect effect on job performance through work engagement, psychological well being has an indirect effect on job performance through work engagement.